2020
DOI: 10.1177/1073858420960111
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and the Neurobiology of Prosocial Behavior

Abstract: Humans are an unusually prosocial species, who engage in social behaviors that include altruism—whereby an individual engages in costly or risky acts to improve the welfare of another person—care, and cooperation. Current perspectives on the neurobiology of human prosociality suggest that it is deeply rooted in the neuroendocrine architecture of the social brain and emphasize the modulatory role of the neuropeptide hormone oxytocin. In this review, we provide a conceptual overview of the neurobiology of prosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 155 publications
(105 reference statements)
0
49
0
5
Order By: Relevance
“…The nucleus accumbens, which has a role in this response during listening to music [35], is also one of the brain regions activated when individuals are performing reciprocally collaborative tasks that are rewarding and empathic [36,37], corroborating the hypothesis of music as "social glue". There is, indeed, direct evidence not only for the causal role of dopamine in pleasure response when listening to music as compared to highly rewarding hedonic experiences, but also for the stimulation of oxytocin and the consequent inducement of prosocial behavior [38][39][40][41]. Neuroimaging, neuropsychological and brain stimulation studies in musical anhedonia (the inability to find music pleasurable) also seem to suggest that human appreciation of music emerges from the predictive process of auditory perception, which connects to the structures involved in the brain's dopaminergic reward system, to the extent that it may function as a stimulus for verbal episodic memory and learning [42][43][44].…”
Section: Music-language Universality and The Biocultural Origins Of Musicmentioning
confidence: 99%
“…The nucleus accumbens, which has a role in this response during listening to music [35], is also one of the brain regions activated when individuals are performing reciprocally collaborative tasks that are rewarding and empathic [36,37], corroborating the hypothesis of music as "social glue". There is, indeed, direct evidence not only for the causal role of dopamine in pleasure response when listening to music as compared to highly rewarding hedonic experiences, but also for the stimulation of oxytocin and the consequent inducement of prosocial behavior [38][39][40][41]. Neuroimaging, neuropsychological and brain stimulation studies in musical anhedonia (the inability to find music pleasurable) also seem to suggest that human appreciation of music emerges from the predictive process of auditory perception, which connects to the structures involved in the brain's dopaminergic reward system, to the extent that it may function as a stimulus for verbal episodic memory and learning [42][43][44].…”
Section: Music-language Universality and The Biocultural Origins Of Musicmentioning
confidence: 99%
“…Evolutionary psychologists typically focus on the "ultimate causes" of human prosociality and explain prosocial behavior in terms of natural selection (Burnstein et al, 1994;Burum et al, 2020;Goetz et al, 2010;van Vugt & van Lange, 2006), whereas medical scientists focus on biological or chemical mechanisms (e.g. oxytocin; de Dreu et al, 2010;Marsh et al, 2020), and neuroscientists investigate activation in certain brain areas when people respond to prosocial decisions (Cutler & Campbell-Meiklejohn, 2019;Genevsky et al, 2013;Harbaugh et al, 2007;Mayr et al, 2009).…”
Section: What Are Underlying Psychological Mechanisms?mentioning
confidence: 99%
“…Current perspectives on the neurobiology of visual face processing suggest that it is deeply rooted in the neuroendocrine architecture of the social brain. The hypothalamic neuropeptide hormone oxytocin (OXT) modulates a broad repertoire of social behaviors, including social communication, interpersonal trust, and prosocial decision-making (6)(7)(8) in a person-specific and contextdependent manner (9). An extensive body of research supports the idea that OXT influences early stages of social information processing (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…With previous neuroimaging studies showing that OXT consistently targets reward-[ (30)(31)(32), but see (33)] and fear-related neurocircuits (34)(35)(36)(37), the peptide possibly facilitates attention to social stimuli by modulating the rewarding experience from interpersonal interactions (18,38), and this experience may be particularly pronounced during encounters with familiar others. In this context, however, it is important to note, that the effects of OXT are highly susceptible to individual personality traits and situational variables (9,39). For example, it has been found that OXT increases envy and gloating (40), decreases the tendency to cooperate in individuals with borderline personality disorder (41), and selectively increases the pleasantness of interpersonal touch in individuals scoring low in autistic-like traits (42).…”
Section: Introductionmentioning
confidence: 99%